Neutral Carrier Ca2+-Microelectrode - M. Oehme; M. Kessler; W. Simon (CHIMIA)
The use of a synthetic electrically neutral ion carrier in Ca2+- selective microelectrodes is described. High ion-selectivities especially in respect to Na+ and Mg2+ as well as a long lifetime of the electrodes open new possibilities for a wide range of intracellular measurements of ion activities.